(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aimed to estimate the impact of economic indicators on inflation in the agricultural sector in Iraq. Time series data were collected for the period (1990-2022) for the variables included in the model, and the ARDL model was used to analyze the data and to determine economic indicators on inflation in the agricultural sector, including agricultural GDP and agricultural employment. agricultural imports, the exchange rate, and agricultural investment, The results showed that there is an inverse relationship for the inflation rate with agricultural domestic product and agricultural labor wages, and it was also shown that there is a direct relationship for the inflation rate with agricultural imports, the exchange rate and agricultural investment. The research recommended supporting agricultural production prices and providing subsidies for agricultural production requirements in order to increase local production and reduce Imported inflation, as support and subsidies are a means of controlling inflation rates and developing import policies and strategies to control inflation rates in the agricultural sector in Iraq, especially for agricultural and food commodities.